2011
DOI: 10.1176/appi.ps.62.9.1047
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Collaborative Depression Management at Community-Based Primary Care Clinics: An Evaluation

Abstract: Objective This study evaluates a large demonstration project of collaborative care in community health centers by examining the role of clinic site on measures of the implementation process and on clinical outcomes that are not accounted for by characteristics of the patients served. Methods This quasi-experimental study examines data on the treatment of 2821 patients over three years at six organizations that implemented collaborative depression care. Outcome data included two quality indicators (receipt of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 15 publications
4
46
1
Order By: Relevance
“…This study's findings are consistent with results from a larger study that demonstrated that community-based organizations that successfully implement collaborative care can achieve meaningful improvements in process and outcomes of care. 7 Practice transformation was facilitated by disaster recovery activities that included training programs to promote implementation of CCMs as well as community-wide demonstration projects to support capacity building and to finance care coordination for an underserved population. The need for integrated services and proactive screening of patients for depression was clearly substantiated by the prevalence of moderate-to-severe depression symptoms and mental health disorders diagnosed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's findings are consistent with results from a larger study that demonstrated that community-based organizations that successfully implement collaborative care can achieve meaningful improvements in process and outcomes of care. 7 Practice transformation was facilitated by disaster recovery activities that included training programs to promote implementation of CCMs as well as community-wide demonstration projects to support capacity building and to finance care coordination for an underserved population. The need for integrated services and proactive screening of patients for depression was clearly substantiated by the prevalence of moderate-to-severe depression symptoms and mental health disorders diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study examining collaborative care for depression in community health centers, participating organizations displayed significant variability in their ability to enact system-level practice changes, as evidenced by differences in quality indicators and outcomes, despite receiving similar training and resources to do so. 7 Little is known about how to implement such changes outside of well-controlled clinical trials. This article describes the practice transformation and quality improvement context of a community health center that offers colocated primary care and mental/behavioral health services.…”
mentioning
confidence: 99%
“…Buy-in from all team members, including administrative, nursing, and other staff, is essential, and "champions" within any of these areas can spark enthusiasm and make the system work more efficiently. An interesting multisite study (26) highlighted the effects that these intangible differences can have. All sites received the same training and postimplementation support, and they had similar patient characteristics, but they demonstrated remarkably different outcomes, presumably as a result of these other influences.…”
Section: The Psychiatrist's Roles In the Collaborative Care Modelmentioning
confidence: 99%
“…Similarly, an increase in the number of urban sustainability networks, during the same period, denotes the desire of local governments to cooperate, exchange knowledge and best practices, and be part of a global SD movement [72].…”
Section: Urban Sustainability Planning and Implementation Gapmentioning
confidence: 99%
“…The focus then will center on testing the concepts and measures of economic, ecological, and social productivity in the urban context, through the application of the urban productivity framework on case studies in Canada. During this research we will utilize "Pando|Sustainable Communities", www.pando.sc, a web-based, multilingual, and fully-featured collaboration platform designed as a place for sustainability researchers and practitioners globally to meet, share ideas and work towards common SD and SCD goals [72]. Through the Pando network we will both disseminate our work and invite colleagues around the world to pilot our framework with communities in their own countries.…”
Section: Conclusion and Further Researchmentioning
confidence: 99%